Gene-Guided Treatment Decision-Making in Non-Small Cell Lung Cancer – A Systematic Review - Saarenheimo, Jatta; Andersen, Heidi; Eigeliene, Natalja; Jekunen, Antti (Frontiers in Oncology, 2021)
Decision-making in cancer treatment is part of clinicians’ everyday work, and it is especially challenging in non-small cell lung cancer (NSCLC) patients, for whom decisions are clearly dependent on gene alterations or the lack of them. The multimodality of treatments, involvement of gene alterations in defining systemic cancer therapies, and heterogeneous nature of tumors and their responsiveness provide extra challenges. This article reviews the existing literature to 2021 with extra effort to explore the role of genes and gene-driven therapies as part of decision-making. The process and elements in this decision-making participation are recognized and discussed comprehensively. Genetic health literacy aids are provided as a part of the review. Our systematic review, data extraction and analysis found that with current methods and broad gene panels, patients benefit from early molecular testing of liquid biopsy samples. An estimated 79% of liquid biopsy samples showed somatic mutations based on 8 original studies included in the systematic review. When both liquid biopsy samples and tissue samples are evaluated, the sensitivity to detect targetable mutations in NSCLC increases. We recommend early testing with liquid biopsy. Additional effort is needed for the logistics of obtaining and evaluating samples, and tissue samples should be saved and stored for tests that are not possible from liquid biopsy.